Pengaruh Pendidikan Kesehatan Tentang Pernikahan Dini terhadap Tingkat Pengetahuan dan Sikap Remaja di Puskesmas Kuala Kec. Kuala Kab. Langkat Tahun 2022 - Dewi Julianti; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Ani Susanti Ndruru (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Early marriage is a marriage that occurs at an age below the ideal provisions, where the prospective bride and groom are generally not physically, mentally, or financially ready. Therefore, early marriage is often considered a hasty decision because it is carried out without proper planning and preparation. The purpose of this study is to determine whether there is an effect of health education about early marriage on the level of knowledge and attitudes of adolescents at the Kuala Health Center, Kuala District, Langkat Regency in 2022. The type of quasi-experimental research with a research design using one group pre-post design, namely This type of research is used to determine the effect of health education about early marriage on the level of knowledge and attitudes of adolescents. This research was conducted at the Kuala Health Center, Kuala District, Langkat Regency in 2022. The population in this study amounted to 30 people, then the sample was part of all the objects studied and was considered to represent the entire population. The number of samples used was 30 people using the Total Sampling technique. The results of the statistical test results using the Wilcoxon test obtained the results of the p value of knowledge = 0.000 <0.05 and the p value of attitude = 0.000 <0.05. So it is proven that there is a significant influence between health education about early marriage on the level of knowledge and attitudes at the Kuala Health Center, Kuala District, Langkat Regency in 2022.